Quantifying the influence of eucalyptus bark and corncob biochars on the physicoâchemical properties of a tropical oxisol under two soil tillage modes - Boris Merlain Djousse Kanouo; Suzanne Edith Allaire (International Journal of Recycling of Organic Waste in Agriculture)
Purpose This study aimed to assess the impact of two biochars applied at the rate of 15 t haâ1 on physico-chemical parameters of an oxisol in Cameroon. Method The biochars were made from slow pyrolysis (~300 °C, 4 h) of eucalyptus tree bark and corncobs and then incorporated into the top 15 cm of the soil with or without straw. The soil tillage mode was either fat plots or furrows and ridges. Soil porosity, bulk density, saturated hydraulic conductivity, available water content, pH, nitrogen, potassium, phosphorus, cation exchange capacity and electrical conductivity were analyzed before biochar application, then 6 and 12 months after. Results None of the measured soil physical parameters were affected by the presence or type of biochar. The total porosity was lower during the second production period compared to the first, while available water content and van Genuchten parameters increased during the second production period. No significant difference was observed between soil nitrogen, phosphorus, potassium, cation exchange capacity and electrical conductivity of control and treated plots. Conclusion We recommend that straw be pyrolysed and the resulting biochar incorporated into soil instead of burying straw (as is actually done in furrow and ridges tillage mode).